O055 Flow limitation and sleepiness in individuals without sleep apnea. (9th November 2022) - Mann, D; Georgeson, T; Azarbarzin, A; Wellman, A; Redline, S; Terrill, P; Sands, S
Abstract: Introduction: Moderate-Severe Obstructive Sleep Apnea (OSA, AHI>15) disturbs sleep through frequent bouts of apnea and is associated with daytime sleepiness. However, many individuals without moderate or severe OSA (i.e. AHI≤15) also report sleepiness. We propose that sleepiness may be a consequence of substantial flow limitation, even in the absence of overt reductions in airflow (apnea/hypopnea). Methods: 2060 participants from the MESA sleep cohort were analysed using our validated method to estimate frequency of certain flow limitation from the airflow signal. Individuals with Epworth Sleepiness Scale ≥11 points were considered 'sleepy'. Logistic regression was conducted to investigate the association between sleepiness (binary dependent variable) and frequency of flow limitation (continuous) in individuals without moderate-to-severe OSA AHI≤15. Models were adjusted for age, sex, race, BMI and self-reported sleep duration. Results: N=832 individuals with AHI≤15 were included in primary models: The odds ratio (OR) for flow limitation predicting sleepiness was 2.14 (CI 1.27-3.61, per 2SD increase in flow limitation frequency i.e. +11% of sleep) and 2.08 (1.19-3.64) when adjusted for AHI. No association between flow limitation and sleepiness was observed in moderate-severe OSA (AHI>15, OR=1.01, 0.7-1.46). Discussion: In individuals with few scored respiratory events (non-OSA and mild-OSA), increased flow limitation frequency by 2 SD (11% of sleep) is associated with a 2-fold increase in risk for sleepiness. Increasing flow limited breaths by 11% increases the odds for being sleepy equivalent to 1.2 hrs less sleep. Flow limitation may be an independent target for ameliorating sleepiness even in the absence of OSA.